Diseño audiovisual de los encantos turísticos que posee el Cantón Mejía - Yánez Calderón, Carlos Luis (2018)
This research project is aimed to elaborate an audiovisual product of the tourist charms that Mejía Canton possesses, using the technique of audiovisual graphics with the purpose of potentiating tourism and disseminating in traditional and alternative media. This documentary video will be a material of social diffusion within the audiovisual field which will be used to help the non-profit community, generating research that sustains what has been learned in the Computer Graphic Design Career. The Bruce Archer method was used, which consists in obtaining graphic pieces, animated texts, images, sounds and illustrations for the elaboration of the audiovisual product; this method is detailed, exhaustive and it will help chronologically in the construction of the proposal. This project is based on a bibliographical-documentary, descriptive and field research; the data collection techniques were surveys and interviews conducted with residents and tourists; likewise, through the statistical method, the data collected could be interpreted. All the aforementioned has allowed concluding that the elaboration of a documentary video of the tourist sites owned by the Mejía Canton is necessary to boost tourism.